THEMATIC STRUCTURES IN STUDENTS' RESEARCH PAPERS AND ORAL PRESENTATIONS:A Case Study of Postgraduate Program in English Education at UPI Bandung - Nugraha, Sidik Indra (2014)
ABSTRACT This research aims to investigate the thematic structures in students' research papers and oral presentations. Specifically, it focuses on two aspects, i.e. types of Theme and realizations of topical Theme in students' research papers and oral presentations. It is qualitative in nature, and involves three students' research papers and transcribed students' oral presentations as the main research data. Findings from the research show differences of thematic structures in students' research papers and oral presentations in terms of the types of Theme used and realizations of topical Theme. Firstly, the types of Theme used in students' research papers and oral presentations were interpersonal, textual, and topical. Topical Theme was the most frequently used type of Theme, with the total of 72.7% and 56.3% in students' research papers and oral presentations respectively. After topical Theme came textual Theme, constituting 26.1% and 39.5% of overall Themes in both types of text respectively. Finally, interpersonal Theme was the least common type of Theme found in students' research papers (1.2%) and oral presentations (5.2%). Secondly, the topical Themes in both types of text were realized by relatively similar elements including nominal group with common or proper noun as Head, nominal group with personal pronoun as Head, nominal group with nominalization as Head, prepositional phrase, nominal group with proper noun as Head, dependent clause, adverbial group, non-representational it, reference item, existential, embedded clause, and question word. Of these twelve elements realizing the topical Themes, nominal group with common noun as head mostly occurred in students' research papers (46.1%) and oral presentations (40.3%). Considering these findings, it is concluded that the variation regarding the types of Theme and realizations of topical Theme in both types of text may be attributed to the mode variation of the texts, i.e. distinction between spoken and written language. This variation of thematic structure is related to the role the language plays in the realization of the context of situation, in this case, students' research papers and oral presentations. It is recommended that teaching on the way the message is organized in both written and spoken contexts of language use be given to students to improve coherence and cohesion of text. Keywords: Theme, students' research papers and oral presentations, mode ABSTRAKSI Penelitian ini bertujuan untuk menginvestigasi struktur tematis dalam tulisan ilmiah dan presentasi lisan mahasiswa. Secara spesifik penelitian ini menyoroti dua aspek, yakni, jenis Theme dan realisasinya dalam tulisan ilmiah dan presentasi lisan mahasiswa. Penelitian ini menggunakan metode kualitatif dan melibatkan masing-masing tiga tulisan ilmiah dan presentasi lisan mahasiswa sebagai data penelitian. Hasil analisis menunjukan perbedaan struktur tematis dalam tulisan ilmiah dan presentasi lisan mahasiswa. Pertama, jenis Theme yang digunakan dalam tulisan ilmiah dan presentasi lisan mahasiswa adalah interpersonal, textual, dan topical. Topical Theme merupakan jenis Theme yang paling banyak muncul, yaitu, 72,7% dalam tulisan ilmiah siswa dan 56,3% dalam presentasi lisan mahasiswa. Berikutnya adalah textual Theme dengan persentase 26.1% dan 39.5% di kedua jenis teks secara berurutan. Interpersonal Theme adalah jenis Theme yang paling jarang muncul, dengan persentase 1,2% dalam tulisan ilmiah dan 5.2% dalam presentasi lisan mahasiswa. Kedua, topical Theme direalisasikan dengan elemen yang sama di kedua jenis teks termasuk nominal group with common or proper noun as Head, nominal group with personal pronoun as Head, nominal group with nominalization as Head, prepositional phrase, nominal group with proper noun as Head, dependent clause, adverbial group, non-representational it, reference item, existential, embedded clause, and question word. Dari keduabelas elemen tersebut nominal group merupakan elemen yang paling sering muncul, 46.1% kemunculan dalam tulisan ilmiah dan 40.3% dalam persentasi lisan. Dari temuan diatas dapat disimpulkan bahwa variasi jenis Theme dan realisasinya di kedua jenis teks dapat disebabkan oleh variasi modus di kedua jenis teks, yakni, bahasa tulis dan lisan. Variasi tematis berhubungan dengan peran bahasa dalam merealisasikan konteks situasi. Dalam pengajaran bahasa siswa harus diajarkan cara menyusun teks dalam kedua jenis modus, lisan dan tulisan, yang benar sehingga mereka mampu menulis teks yang kohesif dan koheren. Kata kunci: Theme, tulisan ilmiah dan presentasi lisan mahasiswa, modus